The Current Situation and Learning Strategies of Foreign Students in Chinese Learning Following Entrepreneurial Psychology - Tang, Min (Frontiers in Psychology, 2022)
Based on entrepreneurial psychology, the current situation of foreign students' use of learning strategies in Chinese learning is explored, the overall situation of learning strategies in this process is analyzed, and the relationship between foreign students' use of learning strategies and various factors are obtained through the designed questionnaire survey. First, a questionnaire suitable for the research respondents is designed to investigate the current situation of foreign students' use of learning strategies in Chinese learning; second, 200 questionnaires are distributed, and 195 questionnaires are recovered, with a recovery rate of 97.5%. After the invalid questionnaire is excluded, the effective rate is 95%; furthermore, the reliability of the questionnaire data is analyzed by SPSS25 software, and Cronbach's α coefficient is 0.869, which proves that the questionnaire has high reliability; finally, the overall situation of foreign students' use of learning strategies in Chinese learning is analyzed from the aspects of their majors, their levels of Chinese proficiency, Chinese learning time, age and personality. The results show that the frequency of using cognitive strategies in learning Chinese is the highest, with a score of 3.689; There is a positive correlation between the use of learning strategies and the degree of proficiency of Chinese; Among them, the foreign students who have studied for 2-3 years use learning strategies the most frequently, and the students aged 28-32 use learning strategies the most frequently in the Chinese level test4. This study provides new ideas for foreign students' Chinese teaching and has a certain reference for foreign students' Chinese teaching strategies.